Pukepuke Fonua: An Exploratory Study on the Faikava as an Identity Marker for New Zealand-Born Tongan Males in Auckland, New Zealand - Fehoko, Edmond Samuel (Auckland University of Technology, 2014)
This thesis is an exploratory study of the experiences and perceptions of a group of New Zealand-born Tongan males living in Auckland on what participation in the Tongan cultural practice of the faikava meant to them, how they valued this experience and whether they believed participation could help minimise some of the social pressures Tongan youth face today – such as alcohol and drug abuse and youth gang affiliation. Reports indicate that a factor in New Zealand-born Pacific Island youth engaging in these and other risky behaviours in New Zealand is their lack of cultural identity and security. As a Tongan, raised in a traditional Tongan family in New Zealand, I had learnt the lea (Tongan language) and anga fakatonga (Tongan culture). This knowledge had been reinforced when I participated in the faikava with my father from a young age. For this study, I wanted to see if the faikava experience which is often regarded as a purely recreational situation and ‘waste of time’ could be a place for cultural reinforcement and maintenance for other New Zealand-born Tongan males as well. The methodological framework of phenomenology and talanoa was employed in this study involving individual talanoa with 12 participants who were members of faikava clubs in the Auckland region. These clubs were mainly linked to churches, villages and old boys associations. The talanoa were conducted in Tongan and English and were recorded. Findings were that the faikava played a significant role in teaching and reinforcing the pukepuke fonua or maintaining the lea and anga fakatonga for this group. In fact, they referred to the faikava as a cultural classroom where through engagement in debates, songs and music, they learnt, rejuvenated and maintained the lea and anga fakatonga. In summary, the faikava was a supplementary education site. In addition, this cultural practice also fostered intergenerational harmony, as the elders passed on customary knowledge. They also listened to the views of these younger participants. Finally for this group, the faikava had served as a diversion from alcohol consumption and affiliation with youth gangs. All 12 participants affirmed the value of the faikava and hope that this would be maintained in the future. On the basis of the results of this research, it can be concluded that the faikava is serving as an identity marker for New Zealand-born Tongan males today. This is a place where the Tongan language and culture is learnt, reinforced and maintained. As this study does not represent the total population of New Zealand-born Tongan males living in the Auckland area, further research is warranted.
Keywords: Faikava; Tongan culture; New Zealand-born Tongans; Inter-generational harmony; Alternative to alcohol; Identity; Cultural reinforcement; Cultural maintenance